Chemical Compound Identification of Lactic Acid Bacteria (LAB) From Porang Tubers Waste (A. muelleri blume) as Probiotic - Hidayat, Habibi; Nakita Heniar Septyana; Riang Adeko; Dinda Rizki Febriani; Amri Setyawati1 (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2024)
The production of amylase produced by lactic acid bacteria (LAB) has better stability. The purpose of this study was to utilize and determine the characteristics of LAB isolates from porang skin waste which have the potential as probiotics and the activity of amylase enzymes. Isolation was done by fermentation method for 48 h with the addition of starter Pediococcus acidilactici that had been cultured. The results showed that the number of colonies of N1 isolates was 49 ×108 CFU/mL with regular small round colonies, having a convex elevation, the edges of the colonies were round, yellowish white, and Gram positive bacteria because they produced a purple color on Gram staining. Acid resistance test at pH 2.0; 3.0; 4.0; 5.0 and 6.0, the isolates N1 was able to survive at each pH because it showed turbidity in the growth medium. The antimicrobial activity test showed a strong zone of inhibition on S. aureus and S. pyogenes of 10,33 and 11,17 mm and a moderate zone of inhibition on K. pneumoniae, S. dysentriae, and P. aeruginosa, respectively, which was 6,33; 7,7 and 7,5 mm. The positive N1 isolate contained alkaloids as bioactive compounds from the results of phytochemical screening and the results of the FTIR analysis showed that specific groups of alkaloids were N-H, C-N, and C=O at wave numbers 3423.30 cm-1; 1235.45 cm-1; and 1634.81 cm-1.